Clinical and functional significance of determining biological age in women during the reproductive period - E. V. Kudryavtseva; D. A. Berezina; V. V. Bazarny; L. G. Polushina; M. А. Kopenkin; A. N. Troitskaya; V. V. Kovalev (Акушерство, гинекология и репродукция)
Introduction. Biological age (BA) reflects the characteristics of the morphological and physiological state of the human body at a specific period of its life.This concept is of particular importance in reproductive medicine, because actual age does not always correlate with the state of organs and systems.Aim: to develop a method for calculating BA for women aged 20–45 years, considering their physiological state and reproductive function.Materials and Methods. A single-stage non-randomized cohort study was conducted. To create the BA calculation model, a study was conducted with 100 healthy women aged 20–45 years. Seventy-eight parameters were analyzed, including anamnesis data, anthropometric parameters, data of general blood test, biochemical blood test, instrumental studies, assessment of overall antioxidant status (ОAS), from which the most informative variables were selected. The model was developed using multiple linear regression.Results. The most informative indicators for calculating BA were: ОAS, static balance time (SBT), body mass index (BMI), and number of former pregnancies. The developed BA calculation formula demonstrated high accuracy, correlating with chronological age (correlation coefficient of 0.947).Conclusion. The proposed BA calculation method is specifically designed for women of reproductive age and shows high accuracy and correlation with chronological age. The inclusion of antioxidant protection parameters, functional state indicators, and reproductive history makes the method versatile and applicable not only in reproductive medicine but also in general medical practice, obstetrics, gynecology, and other fields.